Novel synthesis of porous Mg scaffold as a reactive containment vessel for LiBH4 - Sofianos, M.; Sheppard, Drew; Rowles, Matthew; Humphries, Terry; Liu, Shaomin; Buckley, C. (Royal Society of Chemistry, 2017)
A novel porous Mg scaffold was synthesised and melt-infiltrated with LiBH 4 to simultaneously act as both a confining framework and a destabilising agent for H 2 release from LiBH 4 . This porous Mg scaffold was synthesised by sintering a pellet of NaMgH 3 at 450 °C under dynamic vacuum. During the sintering process the multi-metal hydride, decomposed to Mg metal and molten Na. The vacuum applied in combination with the applied sintering temperature, created the ideal conditions for the Na to vaporise and to gradually exit the pellet. The pores of the scaffold were created by the removal of the H 2 and Na from the body of the NaMgH 3 pellet. The specific surface area of the porous Mg scaffold was determined by the Brunauer-Emmett-Teller (BET) method and from Small-Angle X-ray Scattering (SAXS) measurements, which was 26(1) and 39(5) m 2 g -1 respectively. The pore size distribution was analysed using the Barrett-Joyner-Halenda (BJH) method which revealed that the majority of the pores were macropores, with only a small amount of mesopores present in the scaffol d. The melt-infiltrated LiBH 4 was highly dispersed in the porous scaffold according to the morphological observation carried out by a Scanning Electron Microscope (SEM) and also catalysed the formation of MgH 2 as seen from the X-ray diffraction (XRD) patterns of the samples after the infiltration process. Temperature Programmed Desorption (TPD) experiments, which were conducted under various H 2 backpressures, revealed that the melt-infiltrated LiBH 4 samples exhibited a H 2 desorption onset temperature (T des ) at 100 °C which is 250 °C lower than the bulk LiBH 4 and 330 °C lower than the bulk 2LiBH 4 /MgH 2 composite. Moreover, the LiH formed during the decomposition of the LiBH 4 was itself observed to fully decompose at 550 °C. The as-synthesised porous Mg scaffold acted as a reactive containment vessel for LiBH 4 which not only confined the complex metal hydride but also destabilised it by significantly reducing the H 2 desorption temperature down to 100 °C.